(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In this paper, we study the anisotropic Bianchi type VI0 metric that consists of Tsallis holographic dark energy (THDE) and dark matter (DM). The hybrid expansion law for the average scale factor is used to calculate some cosmological parameters and achieve exact solutions to Einstein's field equations. These parameters geometrical and physical behaviours demonstrate how the universe eventually becomes homogeneous, flat, and isotropic. Analyzing the equation of state (EoS) parameter also reveals that our model acts like a lambda cold dark matter (Λ) scenario in the late universe.